Uma plataforma para disponibilização centralizada de dados abertos governamentais como suporte para aplicações no contexto de cidades inteligentes. - Veira, Daniel Ianegitz (2016)
The Smart City (SC) concept aims to promote dynamic and flexible systems to the cities, that interact with each others and help to maintain the stability and scalability of it’s resources and services, usually through sensors and collectors, with high implantation and maintenance costs. On the other hand, the Open Goverment Data (OGD) are data relationated to the governamental activity, available on the Internet. The publications are fragmented in dierent and uncorrelated portals, also do not follow a standard pattern format. Thus, this work proposes a platform to collect and distribute OGD in a centralized way, in order to provide consolidated information to the context of SC. Also, two validations of this proposal are presented, the first one promoting the solidification of the platform and the second one being an experimental study applied at the academic environment, were eight graduation students where supervisionated, divided into two groups, during the development of two SC projects, consisting of comparative and graphic visualization OGD portals. The experimental group used the platform proposed here as a OGD source, and the control group used OGD collected directly through the governmental transparency portals. At the end of the study, with the intention to find benefits in the utilization of a centralized platform, statistical tests were applied to the collected metrics, and expressive advantages to the experimental group were found, related to the quantity of source-code lines and the development time, indicating that the platform oered benefits during the cycle of development of the project.